Assessment and Monitoring of Salt Affected Soils in Haryana Using Remote Sensing Satellite Imageries - Sharma, R.C.; Bhargava, G.P. (Journal of Soil and Water Conservation, 2022)
Salt affected soils are known to have high potentiality for crop production. Full utilisation of these resources needs quick assessimill about their nature and distribution. Visual interpretation of black and white single band or false colour composite(FCC) Landsat imagery was found effective in mapping salt affected soils and monitoring progress of their reclamation in a part of Haryana state. Using different seasons and bands, it was found that data from May and November particularly of MSS band 5 of Landsat—I and band 2 of Landsat-4 gave the highest information. While the 1 _million scale Landsat imagery led to the identification of salt affected areas (appearing in bright white tone), the enlarged scene of 1:250,000 scale was used in demarcating and estimating the areal extent. The study area comprised 200,000 ha, of which 32,400 ha (16. 2%) was Implied as salt affected. As a result of adoption of technology by the fanner and also various reclamation programmes launched by the State Government, considerable area of salt affected soils was reclaimed and resorted to cropping. Study of , multidate satellite imagery ,for the years 1975 and 1984 showed a considerable reduction in salt affected area, as only 15,810 ha remained un reclaimed in 1984. The reclaimed salt affected soil showed significant improvement in soil properties and also produced good yields of rice and wheat in the first and subsequent years of reclamation